'It's Just about the Crime, Not the Victim': Critical Insights from Australian Service Providers Working with People Who Have Been Trafficked. Issue 1 (1st July 2018) - George, Emma; Tsourtos, George; McNaughton, Darlene
Abstract: Human trafficking is a global public health issue, prevalent in Australia. Our study aimed to gain in-depth understanding of human trafficking and related service provision from a range of sectors, from the perspective of service providers. Adopting a qualitative descriptive approach, in-depth semi-structured interviews were undertaken with 13 service providers from a range of organisations across three Australian states. Service providers emphasised the challenges posed by Australia's predominately criminal justice approach to trafficking, in both policy and service provision, with some suggesting the current process is re-traumatising. Results support refocusing policy and services away from a criminal justice response to a more comprehensive and holistic response that includes greater recognition of the social determinants of health and the provision of tailored services. This requires increased collaboration between service providers, some of whom have very different agendas. The findings provide support for recommendations with the Australian government inquiry into modern-day slavery and therefore have important implications for policy and health services nationally to become more holistic in responding to human trafficking.